Answer:
Given: In triangle ABC , AD is drawn perpendicular to BC.
Since AD is drawn perpendicular to BC, it creates two right triangles: ADB and ADC.
Prove that: [tex]AB^2-BD^2 = AC^2-CD^2[/tex]
Pythagoras triangle for right angle, the square of the length of the hypotenuse is equal to the sum of the squares of the lengths of the legs.
In a right angle triangle ADB;
[tex]AD^2+BD^2 = AB^2[/tex] [By Pythagoras theorem]
or
[tex]AD^2= AB^2-BD^2 [/tex] .......[1]
Now, in right angle triangle ADC;
[tex]AD^2+CD^2 = AC^2[/tex] [By Pythagoras theorem]
or we can write this as;
[tex]AD^2= AC^2-CD^2 [/tex] ......[2]
Substituting the equation [1] in [2] we get;
[tex]AB^2-BD^2 =AC^2-CD^2 [/tex] hence proved!